Death and community - Božić Blanuša, Zrinka (Array, 2010)
According to Jean-Luc Nancy, the most painful testimony of modern world is the testimony of the dissolution, the dislocation, or the conflagration of community. This failure of communal models (communism, liberalism, Christianity) is linked to their dependence on the notion of human immanence (totality, self-presence, self-consciousness). Thanks to the rejection of the metaphysics of the subject, the community cannot be described as a communion of individuals joined in some higher totality. In Nancy's view, the community is not a result of some project, it happens to singular beings (not individuals) and their communal relation is determined by something incommunicable that we all share - death. In his response to Nancy, Blanchot also addresses the problem of death and challenges the Heideggerian analythic of mortality that emerged througout the twentieth century. According to Heidegger, death is an individual engagement: Mitsein is an essential structure to the constitution of selfhood, but death belongs exclusively to the solitary Dasein. Although the fate of Dasein is communal, it takes no part in the Other's relation to its anticipation of death. This means that we do not experience the dying of others in genuine sense, but we are, at the very most, just there. In contrast to this attitude, Blanchot argues that the self's relation to its own death is an exposure that opens onto the death of the other person. The self is brought outside of itself and into the community by way of its relation to the Other's finite existence. Therefore, the community is, in Blanchot's view, grounded precisely by the self's relation to the death of the other person. Nancy claims that all present writing responds in some way to the testimony of absence of community. The core of this crisis is the Western philosophy's inability to think community beyond the subject as its organizing category. But what if, death, which announces the finitude of the subject, becomes a foundation for a different conception of community? The purpose of this paper is to explore how in a dialogical exchange between Heidegger, Nancy and Blanchot death emerges as a common ground for rethinking of community.